THE KUYTUN VALLEY AS AN EXOGEODYNAMIC TEST SITE FOR PRACTICING THE APPLICATION OF METHODOLOGY FOR INTERDISCIPLINARY RESEARCH IN THE SEDIMENTATION SETTINGS OF LOESS-LIKE COVER DEPOSITS IN THE LATE PLEISTOCENE TRANSBAIKALIA - G. G. Matasova; A. Yu. Kazansky; A. A. Shchetnikov; I. A. Filinov (Геодинамика и тектонофизика)
An interdisciplinary research in the Late Quaternary loess-like cover deposits in the valley of the Kuytunka River (Western Transbaikalia) was aimed at reconstructing the conditions and dynamics of regional sedimentation. Particular attention is paid to assessing the information capacity of the methods involved therein: lithofacies analysis, grain-size analysis, and petromagnetic and lithochemical analyses. It is shown that the results of each method independently provide additional information on the processes of sedimentation, are not duplicated, and make it possible to obtain a full characterization of the factors and features of sedimentogenesis. It was found that the valley sedimentation was of cyclic character: warm (soil formation) periods changed to the periods of cooling-(accumulation of sandy-loamy strata); all processes occurred predominantly in semi-arid climate with slight fluctuations in humidity. The mode of the normal formation of a blanket of sedimentary material manifests itself in the structure and properties of deposits exposed on the southern slope of the valley (Kuytun-1 section). Intensive slope processes, and reworking and remixing of sediments on the gentle valley north-exposure slope by catastrophic flows (slope mudflows) and cryogenesis are reflected in the structure and properties of the deposits exposed in the Kuytun-2 section. There are shown the advantages of an integrated approach for detailing the structure of the sections, explaining the genesis of sediments, determining the most probable source areas for the sediment and modes of sediment transport, and reconstructing sedimentary environments.